IMPROVING HEALTH MANAGEMENT FOR HAJJ AND UMRAH PILGRIMS IN INDONESIA: IMPLEMENTATION OF MINISTER OF RELIGIOUS AFFAIRS DECREE NO. 1456/2022 - Mustaqim, Dede Al (Institut Agama Islam Negeri Metro, 2024)
The pilgrimage journey of Hajj and Umrah is a significant moment for Muslims worldwide. However, the complexity and health risks associated with this journey demand adequate protection. Therefore, the Indonesian government through Minister of Religious Affairs Decision Number 1456 of 2022 aims to enhance the health management of Hajj and Umrah pilgrims in the Holy Land. This study aims to determine the implementation of this policy in improving health management for Hajj and Umrah pilgrims in Indonesia. The research utilizes a descriptive-analytical approach. Data were obtained through official government documents and related literature. The results of this study indicate that the implementation of the policy demonstrates that mandating businesses and workers to be registered in the national health insurance program, as well as the registration requirements for prospective Umrah and special Hajj pilgrims, have had a significant impact on improving access to healthcare services for pilgrims. Furthermore, this policy also strengthens the supervision and management of the national health insurance program through the direct involvement of the Director General of Hajj and Umrah Services in guidance and monitoring. Minister of Religious Affairs Decision Number 1456 of 2022 contributes significantly to improving health management for Hajj and Umrah pilgrims in Indonesia. By mandating the registration of active participants in the national health insurance program and enhancing oversight of its implementation, this policy helps ensure that every pilgrim receives adequate health protection during their journey and stay in the Holy Land.